Social figurations and tourist displacement in Argentina - Gómez, Raimundo Elías (2015)
In this paper we analyze, on the one hand; the figurations of transnational tourist travels; and secondly, tourism concepts involving these configurations. We will do it, based on two initial questions: a) the exploration of the profiles movements than affecting tourism in Argentina; and b) the characterization of tourists and tourism in this country, during the period 2009-2014. To achieve our goals, we will use multidimensional statistics, and qualitative analysis of categories. We try to make an approach to the problem, showing that the displacements of people across state territories, are transformations toward explicit new forms of social integration, which are also the stimulators and the centerpieces of tourism industry.